2021
DOI: 10.2147/rmhp.s290135
|View full text |Cite
|
Sign up to set email alerts
|

Health Centers’ Preparedness for Coronavirus (COVID-19) Pandemic in South Wollo Zone, Ethiopia, 2020

Abstract: Background COVID-19 is a highly contagious respiratory disease caused by severe acute respiratory syndrome coronavirus two (SARS-CoV-2). Preparedness of health facilities to prevent the spread of COVID-19 is an immediate priority to safeguard patients and healthcare workers and to reduce the spread of the pandemic. However, the preparedness of health centers in south Wollo zone is unknown. Objective To assess the preparedness of Health Centers for COVID-19 in South Woll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…Students are probably careless and reluctant because of fewer deaths confirmed in Ethiopia. However, this outcome was lower than 26.1% in South Wollo [ 21 ], 54% in North Shoa [ 22 ], and 41.3% in Gondar [ 10 ]. The variation may account for the differences in the target population, study period, outcome measurement, and sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Students are probably careless and reluctant because of fewer deaths confirmed in Ethiopia. However, this outcome was lower than 26.1% in South Wollo [ 21 ], 54% in North Shoa [ 22 ], and 41.3% in Gondar [ 10 ]. The variation may account for the differences in the target population, study period, outcome measurement, and sample size.…”
Section: Discussionmentioning
confidence: 99%
“…The public hospitals' preparedness score was 129 ± 32, which is better than the mean score of health care facilities of Ethiopia where the mean score was 70.3 ± 21.6 [17]. In the same study, it was concluded that 73.9% of the health centers still had insufficiencies and fell in the "work to do" category; conversely, the score of no health facility fell below this [17]. Zia and his colleagues predicted poor performance of the local health system during the crisis, pertaining to sub-standard execution of the coordination, operational and procedural aspects [18].…”
Section: Discussionmentioning
confidence: 69%
“…Tiruneh and his colleague showed that 37.5% of hospitals in North-West Ethiopia had an 'unacceptable' level of preparedness, 12.5% had an acceptable level, and the remaining 50% of hospitals had insufficient levels of preparedness [7]. The public hospitals' preparedness score was 129 ± 32, which is better than the mean score of health care facilities of Ethiopia where the mean score was 70.3 ± 21.6 [17]. In the same study, it was concluded that 73.9% of the health centers still had insufficiencies and fell in the "work to do" category; conversely, the score of no health facility fell below this [17].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“… 27 This may be due to the low preparedness of health centers to cope with the changing realities during emergencies like COVID-19, as only 26% of facilities in Ethiopia were deemed prepared to cope with the disease and the preventive principles of COVID-19 might not be practiced properly. 28 Fear of getting the infection due to physical proximity may have also limited the readiness of women to go for health care early. 29 …”
Section: Discussionmentioning
confidence: 99%